Evaluation of Locally Available Fuller’s Earth for the Bleaching of Soybean Oil (Biological Sciences - PJSIR, 2006)
Locally available Fuller’s earth was investigated for bleaching soybean oil. Investigations showed that raw earth samples possessed desirable physical properties and consisted of the clay minerals suitable for bleaching edible oils. The Fuller’s earth sample was also activated by refluxing with 4 N hydrochloric acid for 3 h at 100 °C. Fresh volumes of soybean oil were bleached with 3% of the activated earth and its bleachibility was determined by Lovibond tintometer. The efficiency of bleachability was compared with that of Tarana Optimum, the standard bleaching earth of German origin for comparison. It was found that bleachibility of the activated earth samples and that of Tarana Optimum was quite comparable.